Pengembangan Modul Pembelajaran Berbasis Problem Solving pada Materi Gerak dan Gaya Kelas VIII SMP - El Arni Deti; Husna Husna; Megasyani Anaperta (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
This study aims to develop a physics learning module based on problem solving that is valid and practical on the material of motion and style for grade VIII students of SMP Negeri 16 Kerinci. The research method used is the development of a 4-D model (Define, Design, Develop, and Dessiminate). The define stage consists of syllabus analysis, textbook analysis, literature review analysis, student and educator interviews. At the design stage, the product design is carried out, namely the module, then at the develop stage, the module validation test is carried out by 2 validators. Practicality test by 1 physics educator and 24 class VIII B students of SMP Negeri 16 Kerinci. Based on the results of the study, it was obtained that the average value of the module validity test by three validators was 97.03% with the very valid category. While the practicality test with respondents consisting of one educator and class VIII B students totaling 24 people was obtained 91.63% with the very practical category. So it can be concluded that the physics learning module based on Problem Solving on the motion and style material of the VIII grade students of SMP Negeri 16 Kerinci which is produced has been categorized as valid and practical.